MILLIMETER AND TERAHERTZ WAVE SCATTERING DIAGRAMS IN RAINS - V. L. Kostina; Yu. I. Malyshenko; A. N. Roenko (Радиофизика и электроника, 2015)
Detailed information about millimeter and terahertz wave scattering diagrams in rains is needed to develop millimeter and terahertz range radio engineering systems. It is rather difficult to measure scattering diagrams, the easier way is to calculate them. The prepared tables of scattering diagrams can be used for microwave range, but there are no such data for the terahertz one. This paper presents the results of scattering diagram calculation of millimeter and terahertz waves by raindrops. The calculations were using the exact formulas for all interval of raindrop sizes appeared in precipitation. Data base of scattering diagrams was developed on the basis of obtained results. It gives a wide opportunity for calculation scattering diagrams at various combination of initial data, i.e. radiation wave length, raindrop size distribution function and rain intensity value. The obtained results may be used for estimation of radiation power spatial distribution in millimeter and terahertz ranges.